Effect of Reward Politics on Strategy Implementation at the Kenya Power and Lighting Company in Nairobi County, Kenya - Matiki, Jimjohn; Lanoi, Rahab; Mwangi, Elias (European Journal of Business and Strategic Management, 2024)
Purpose: The aim of the study was to examine the effect of reward politics on strategy implementation at the Kenya Power and Lighting Company in Nairobi County, Kenya. Methodology: This study was guided by the upper echelon’s theory, strategic contingency theory, Elite Theory and Mintzberg’s political theory. Descriptive survey research design was adopted in the study. The target population included 9,655 employees working at the Kenya Power and Lighting Company Headquarters. Stratified random sampling method was used to select a sample size of 373 employees that were arrived at using the Krejcie and Morgan (1970) table of sample size determination. Questionnaires were the main instrument of data collection. A pilot study was conducted in order to check the validity and reliability of the instrument. Primary data collected was analysed using both descriptive and inferential statistics and with the help of the Statistical Package for Social Sciences version 25. The descriptive statistics comprised of percentages, means, and standard deviation and were presented using frequency tables, pie charts, and bar graphs. Inferential statistics comprised of both correlation and multiple linear regression analysis. These statistics helped to establish the relationship between the independent and dependent variables of the study. Findings: The findings of the study showed that reward politics and strategy implementation had a positive and significant coefficient (b=0.017, p Value<0.05). The study concluded that all the components of organization politics (reward politics, factionalism, gatekeeping politics, and territorialism) had a statistically significant influence on strategy implementation at the Kenya Power and Lighting Company. Unique Contribution to Theory, Practice and Policy: The study was anchored on upper echelons theory. The study recommended that the Board of Directors should oversee the implementation of policies that discourage territorialism within the company. Clear guidelines for resource allocation and accountability measures should be established to ensure that resources are distributed based on strategic needs rather than individual territorial interests.